2018
DOI: 10.1590/1678-7757-2017-0367
|View full text |Cite
|
Sign up to set email alerts
|

In-office tooth bleaching with 38% hydrogen peroxide promotes moderate/severe pulp inflammation and production of ll-1β, TNF-β, GPX, FGF-2 and osteocalcin in rats

Abstract: Objectives:To study the intensity of inflammatory infiltrate and production of interleukin-1β (ll-1β), tumor necrosis factor-β (TNF-β), fibroblast growth factor-2 (FGF-2), glutathione peroxidase (GPX), and osteocalcin in response to in-office tooth bleaching in rats.Material and Methods:Twenty male Wistar rats were randomized into four groups (n=5) according to the received treatment (tooth bleaching or no treatment - control) and the period of euthanasia after treatment (24 h or 10 days). We performed tooth b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
(57 reference statements)
0
17
0
1
Order By: Relevance
“…A previous study in molars of bleached rats showed that a high concentration of HP can cause severe damage to the dental pulp, while low concentrations of HP can induce proliferation in the pulp tissue, which could explain these results. In addition, two studies showed an increase in OCN in the pulp tissue after dental bleaching (19,41), which demonstrates that despite the importance of in vitro studies, different results can be observed from those that occur in in vivo models. In addition, the ROS can accumulate during oxidative stress, but due to their reactivity, this accumulation occurs in a transitory way; however, it can damage essential biomolecules, which can be challenging to recover in cell culture, but reversible in living tissue (42).…”
Section: Discussionmentioning
confidence: 96%
“…A previous study in molars of bleached rats showed that a high concentration of HP can cause severe damage to the dental pulp, while low concentrations of HP can induce proliferation in the pulp tissue, which could explain these results. In addition, two studies showed an increase in OCN in the pulp tissue after dental bleaching (19,41), which demonstrates that despite the importance of in vitro studies, different results can be observed from those that occur in in vivo models. In addition, the ROS can accumulate during oxidative stress, but due to their reactivity, this accumulation occurs in a transitory way; however, it can damage essential biomolecules, which can be challenging to recover in cell culture, but reversible in living tissue (42).…”
Section: Discussionmentioning
confidence: 96%
“…This occurs because the bleaching agent in the form of hydrogen peroxide and its oxidation products have penetrated first through the interprismatic space of the enamel and dentinal tubules into the pulp, resulting in injury to the pulp tissue, this condition results in the number of fibroblasts detected in this group not much different from the number of fibroblasts in the Control Group. This is supported by Silva-Costa et al2 (2018) who stated that the pulp response to bleaching varies from mild to severe inflammatory reactions that can even cause partial necrosis of the coronal pulp tissue. Inflammatory reactions due to oxidative stress caused by ROS can still occur even though the composition of the bleaching gel contains desensitizing agents, namely potassium nitrate and fluoride because hydrogen peroxide has a lower molecular weight so that hydrogen peroxide reaches the pulp more quickly and causes injury and causes an inflammatory response5 .…”
mentioning
confidence: 71%
“…In-office bleaching is a bleaching technique using high concentrations of hydrogen peroxide and has several advantages, for instance the treatment process is very fast and the process is controlled by the dentist, thus the results can be seen in one visit and the patient is more cooperative 1,2 . Hydrogen peroxide as an active bleaching agent is an oxidant, with the help of chemical or physical activators it breaks down into hydroxyl radicals, perhydroxyl radicals, perhydroxyls anions and superoxide anions.…”
Section: Introductionmentioning
confidence: 99%
“…This fact may justify not having noticed a significant reduction in the values of the SpO 2 p reading during the sessions. There was a short period between the bleaching agents' application and the SpO 2 p readings, which might have been insufficient for the installation of an inflammatory process [ 36 ]. On the other hand, there was a period of 7 days between SpO 2 p readings from one session to another, which may have been enough for the inflammatory process to cease.…”
Section: Discussionmentioning
confidence: 99%